Fatigue Behavior of Super Duplex Stainless Steel Exposed in Natural Seawater Under Cathodic Protection - Vucko, Flavien; Ringot, Geoffrey; Thierry, Dominique; Larché, Nicolas (Frontiers in Materials, 2022)
Under operating conditions, alternated loading and fatigue are encountered, controlling the durability and the safety of components and structures made in super duplex stainless steels (SDSS). In particular, the use of a cathodic protection (CP) system, to protect the structure against corrosion, can induce hydrogen charging of the SDSS. Thus, the aim of this work was to investigate the sensitivity of some industrial products made in SDSS 2507 (UNS S32750), without artificial thermal ageing, under test conditions as close as possible to real environments. In situ fatigue tests under alternated 4 point-bending conditions were conducted in natural seawater with and without CP. The fatigue behavior was evaluated as a function of environmental parameters such as the temperature, material parameters, particularly the austenite spacing and microstructure around orbital welds by Tungsten Inert Gas (TIG) welding, and stress concentrations through the presence of surface defects. The fatigue life obtained in air or in seawater at the open circuit potential (OCP) were rather similar. A fatigue life enhancement was systematically observed under CP particularly in the range of low applied load, despite evidence of brittle failure on the fracture surfaces of samples tested under CP. The data suggests immunity of the SDSS to hydrogen embrittlement under present experimental conditions of fatigue testing.